Micropropagation Of Curcuma Aeruginosa And Curcuma Heyneana Using Aerated Culture System - ., Novianti Suwitosari (2012)
Curcuma aeruginosa and C. heyneana aseptic rhizomatous bud explants were established with immersion in 70% (v/v) ethanol for 10 minutes followed by surface-sterilization with 20% (v/v) Clorox® for 20 minutes. This surface-sterilization technique enabled 73.7% and 83.3% of C. aeruginosa and C. heyneana bud explants became aseptic with 66.7% and 87.5% survived explants, respectively. All the aseptic explants when cultured on MS medium supplemented with 2.0 mg/l BA and 0.5 mg/l NAA produced 1.9 shoots per explant for C. aeruginosa and C. heyneana produced 2.1 shoots per explant after four weeks of culture. The shoot explants of C. aeruginosa subsequently produced more multiple shoots when cultured in liquid shoot proliferation medium, while the number of shoots produced from C. heyneana was found to be no different in the gelled or liquid medium.